A simulation method to verify the mechanism of multiple factors affecting TiO2 gas sensing performance
Through the establishment of the TIO2 crystal model and simulation multi -factor effects, the traditional research method was solved by the problem of experimental restrictions, the effect of shortening the test cycle and reducing costs, and explaining the performance improvement of the gas sensor from the atomic level.
Patent Information
- Application Number
- CN202210297541.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-03-24
AI Technical Summary
The prior art is difficult to improve the detection performance of TiO2 gas-sensitive sensors from a mechanism perspective, and traditional research methods are limited by experiments, with long test cycles, high cost and poor results.
By establishing the TIO2 crystal model and TIO2 crystal surface, the effect of simulation method of the calculation method is used to simulate the effects of multi -factor on TiO2's gas -sensitive performance, including testing of gas sensing characteristics, and record the effects of different humidity and metal atom doping on the response value of the gas sensor.
Greatly shortened the test cycle, reduced the cost of the experiment, improved the test effect, and explained the experimental phenomenon from the atomic level, providing theoretical guidance to improve the performance of the gas sensitive sensor.
Smart Images

Figure CN114720511B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of TiO2 materials, and in particular to a simulation method for verifying the mechanism of multiple factors affecting the gas-sensitive performance of TiO2. Background Art
[0002] People's daily production and life are inseparable from the gas environment. With the development of industry, people are paying more and more attention to toxic and harmful gases. The rapid development of China's economy has further enhanced people's safety awareness. Gas sensor instruments for detecting gas safety are in a period of rapid industrial growth. Researching the performance of gas sensors is of great significance for solving human health problems and environmental pollution problems.
[0003] TiO2 is a stable metal oxide. It is cheap, non-toxic and pollution-free. It has good stability, resistance to photochemical corrosion and strong redox ability. It is often used in the preparation of gas sensors. The performance of gas sensors is often affected by different factors, including the preparation method of gas-sensitive materials, the type and concentration of target gas, and humidity changes in the detection environment. These factors make the detection mechanism of gas sensors unclear, making it difficult to improve the detection performance of gas sensors from a mechanism perspective. At the same time, TiO2 doping modification is a current research hotspot for TiO2 gas-sensitive materials, which can improve the performance of gas sensors from the perspective of gas-sensitive material preparation. However, traditional research uses physical objects, which is easily limited by experiments, has a long test cycle, high experimental costs, and poor test results. Summary of the invention
[0004] The purpose of the present invention is to provide a simulation method for verifying the mechanism of multiple factors affecting the gas sensing performance of TiO2. The present invention has small experimental restrictions, can greatly shorten the test cycle, can reduce unnecessary experimental costs, and can effectively improve the test effect.
[0005] To solve the above technical problems, the technical solutions provided by the present invention are as follows: a simulation method for verifying the mechanism of multiple factors affecting the gas sensing performance of TiO2, including the establishment of a TiO2 crystal model, the establishment of a TiO2 crystal surface, and the test of doping and gas sensing characteristics;
[0006] The TiO2 crystal model is a supercell of eight anatase phase TiO2 crystal cells;
[0007] The TiO2 crystal plane is established by sectioning the supercell to obtain the TiO2 (101) plane, and the TiO2 crystal plane is doped by adsorbing water molecules and / or doping metal atoms on the TiO2 (101) plane.
[0008] The gas sensing property test uses an aluminum oxide plate with a gold electrode and a heating layer as a gas sensor substrate, and uses molecularly adsorbed and / or metal atom-doped TiO2 as a gas sensitive material, and records the effects of metal atom doping types and water molecule content on the response value of the gas sensor under different humidity.
[0009] The above-mentioned simulation method for verifying the mechanism of multiple factors affecting the gas sensing performance of TiO2, the supercell is simulated by Materials studio software, the lattice constants are a0=b0=378.4pm, c0=951.5pm, the space group is D4h19-I41 / amd, the plane wave shear energy is set to 340eV, the K-point is 2×3×1; the overall energy level of the unit cell is better than the minimum of 1×10 -5 eV·atom -1 The distance deviation between atoms is 0.001°A; the Kohn-Sham equation and energy functional are solved using SCF to optimize the TiO2 crystal model.
[0010] The aforementioned simulation method for verifying the mechanism of multiple factors affecting the gas-sensitive performance of TiO2 is to cut the supercell to obtain the TiO2 (101) surface, add a vacuum layer with a size of 11.15Å×7.60Å×17.428Å, and use metal atoms to dope the TiO2 (101) surface to replace the Ti atom in the TiO2 (101) surface with a metal atom.
[0011] In the aforementioned simulation method for verifying the mechanism of multiple factors affecting the gas-sensing performance of TiO2, the doping of the TiO2 crystal surface is performed by increasing the concentration of water molecules on the TiO2 (101) surface doped with metal atoms.
[0012] The aforementioned simulation method for verifying the mechanism of multiple factors affecting the gas-sensitive performance of TiO2, the test of the gas sensing characteristics uses H2S as the target detection gas, the H2S concentration in the test is controlled by a mass flow controller, and the humidity level during the test varies from 35%RH-85%RH and is calibrated by a hygrometer.
[0013] Compared with the prior art, the present invention establishes a TiO2 crystal model and a TiO2 crystal plane at the atomic level, and uses the TiO2 crystal model to perform computational experiments on its crystal structure, bandgap width, electronic state density and other characteristics. Through the TiO2 crystal plane, the crystal surface structure, energy band, state density, optics and gas-sensitive properties after molecular adsorption and / or doping with metal atoms can be experimented, and the influence of metal atom doping modification and environmental humidity changes on TiO2 characteristics can be simulated. At the same time, from the perspective of gas-sensitive response mechanism, the performance of the gas sensor is analyzed, which greatly reduces the experimental time and cost. The process of the present invention is not limited by experiments, and the test cycle can be greatly shortened. Existing experimental phenomena can be explained at the atomic level, and unnecessary experimental costs can be reduced by calculating and designing materials, and the performance of the gas sensor can be effectively improved, which provides important theoretical guidance and technical support for the improvement of the performance of the gas sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a model diagram of a water molecule adsorbed on the TiO2 (101) surface.
[0015] Figure 2 This is the bandgap width diagram of TiO2 (101) surface before water molecules are adsorbed.
[0016] Figure 3 This is the bandgap width diagram after a water molecule is adsorbed on the TiO2 (101) surface.
[0017] Figure 4 This is the bandgap width diagram after two water molecules are adsorbed on the TiO2 (101) surface.
[0018] Figure 5 This is the bandgap width diagram after three water molecules are adsorbed on the TiO2 (101) surface.
[0019] Figure 6 This is the response curve of TiO2 to 50ppm H2S under different ambient humidity.
[0020] Figure 7 This is the bandgap width diagram of 0.1M iron atoms doped TiO2 (101) surface before water molecules are adsorbed.
[0021] Figure 8 This is the bandgap width diagram after a water molecule is adsorbed on the TiO2 (101) surface doped with 0.1M iron atoms.
[0022] Fig. 9 This is the bandgap width diagram after 0.1M iron atoms doped TiO2 (101) surface adsorbed two water molecules.
[0023] Fig.10 This is the bandgap width diagram after 0.1M iron atoms doped TiO2 (101) surface adsorbed three water molecules.
[0024] Fig.11 This is the PDOS diagram of undoped TiO2 (101) surface.
[0025] Fig.12 This is the PDOS diagram after a water molecule is adsorbed on the TiO2 (101) surface doped with 0.1M iron atoms.
[0026] Fig.13 This is the PDOS diagram after 0.1M iron atoms doped TiO2 (101) surface adsorbed two water molecules.
[0027] Fig.14 This is the PDOS diagram after 0.1M iron atoms doped TiO2 (101) surface adsorbed three water molecules.
[0028] Fig.15 This is the response curve of 0.1M iron atom-doped TiO2 to 50ppm H2S under different ambient humidity. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.
[0030] Example 1: A simulation method for verifying the mechanism of multiple factors affecting the gas sensing performance of TiO2, comprising the following steps:
[0031] (1) Establishment and optimization of TiO2 crystal model:
[0032] Construct eight supercells of anatase TiO2 crystal structures. Through Materials studio software simulation, set the lattice constants a0=b0=378.4pm, c0=951.5pm, and the space group is D4h19-I41 / amd. All calculations are uniformly based on the DFT+GGA+PBE theoretical model. Set the plane wave shear energy to 340eV and the K-point to 2×3×1; the overall energy level of the unit cell is better than the minimum of 1×10 -5 eV·atom -1 The distance deviation between atoms is 0.001°A; the Kohn-Sham equation and energy functional are solved using SCF to optimize the TiO2 crystal model.
[0033] (2) Establishment and doping of TiO2 crystal surface:
[0034] The optimized supercell was sectioned to obtain the TiO2 (101) plane, and a vacuum layer with dimensions of 11.15Å×7.60Å×17.428Å was added.
[0035] Build a H2O molecular model, such as Figure 1As shown in the figure, the effect of humidity on the sensor is analyzed by increasing the concentration of water molecules on the TiO2 (101) surface. Figure 2-Figure 5 As shown, Figure 2 This is the bandgap width diagram of TiO2 (101) surface before water molecules are adsorbed. Figure 3 This is the bandgap width diagram after a water molecule is adsorbed on the TiO2 (101) surface. Figure 4 This is the bandgap width diagram after two water molecules are adsorbed on the TiO2 (101) surface. Figure 5 This is the bandgap width diagram after three water molecules are adsorbed on the TiO2 (101) surface. Figure 2-Figure 5 It can be seen that when no water is adsorbed, the band gap width of TiO2 is 2.142eV. After adsorbing one water molecule, the band gap width decreases to 1.761eV. As the number of water molecules increases, the band gap width increases to 2.507eV and 2.504eV.
[0036] (3) H2S was used as the target detection gas, and the H2S concentration in the experiment was controlled by a mass flow controller. An alumina plate with a gold electrode and a heating layer was used as the gas sensor substrate, and TiO2 adsorbed with water molecules was used as the gas sensitive material. During the experiment, the humidity level varied from 35%RH to 85%RH and was calibrated by a hygrometer. The effect of water molecule content on the H2S response value of the gas sensor at different humidity levels was recorded. Figure 6 As shown in the figure, as the ambient humidity increases, the response value of the gas sensor to H2S gradually increases, but when the humidity exceeds 70%RH, the response value of the gas sensor drops rapidly. From the perspective of the response mechanism of the TiO2 gas sensor, the smaller the bandgap width of TiO2, the more conducive it is to the transition of its valence band electrons, and the higher its gas-sensitive response value. Combined with the above simulation results, the trend of the bandgap width change is consistent with the experimental results.
[0037] Example 2: A simulation method for verifying the mechanism of multiple factors affecting the gas sensing performance of TiO2, comprising the following steps:
[0038] (1) Establishment and optimization of TiO2 crystal model:
[0039] Construct eight supercells of anatase TiO2 crystal structures. Through Materials studio software simulation, set the lattice constants a0=b0=378.4pm, c0=951.5pm, and the space group is D4h19-I41 / amd. All calculations are uniformly based on the DFT+GGA+PBE theoretical model. Set the plane wave shear energy to 340eV and the K-point to 2×3×1; the overall energy level of the unit cell is better than the minimum of 1×10 -5 eV·atom -1The distance deviation between atoms is 0.001°A; the Kohn-Sham equation and energy functional are solved using SCF to optimize the TiO2 crystal model.
[0040] (2) Establishment and doping of TiO2 crystal surface:
[0041] The optimized supercell is cut to obtain a TiO2 (101) plane, and a vacuum layer with a size of 11.15Å×7.60Å×17.428Å is added. The TiO2 (101) plane is doped with metal atoms Fe, and the Ti atom in the TiO2 (101) plane is replaced with an Fe atom. In other embodiments, Co atoms or Zn atoms may also be used.
[0042] The H2O molecular model was established, and the effect of humidity on the sensor was analyzed by increasing the concentration of water molecules on the iron-doped TiO2 (101) surface. Figure 7-10 As shown, Figure 7 This is the bandgap width diagram of 0.1M iron atoms doped TiO2 (101) surface before water molecules are adsorbed. Figure 8 This is the bandgap width diagram after a water molecule is adsorbed on the TiO2 (101) surface doped with 0.1M iron atoms. Fig. 9 This is the bandgap width diagram after 0.1M iron atoms doped TiO2 (101) surface adsorbed two water molecules. Fig.10 This is the bandgap width diagram after 0.1M iron atoms doped TiO2 (101) surface adsorbed three water molecules. Figures 7 to 10 It can be seen that when no water is adsorbed, the bandgap width of iron-doped TiO2 is 1.425 eV. After adsorbing one water molecule, the bandgap width decreases to 1.325 eV. As the number of water molecules increases to two, the bandgap width increases to 1.493 eV. When the number of water molecules increases to three, the bandgap width decreases again to 1.307 eV. Fig.11 The distribution of the electron state density of TiO2 in the graph can be used to analyze the distribution of each atom. When iron-doped TiO2 (101) is used, Fig.12 As shown in the figure, a new energy level appears near the Fermi level of titanium dioxide, which reduces its bandgap width. Therefore, iron doping is beneficial to the improvement of TiO2's gas sensing performance. At the same time, a new energy level composed of hydrogen atoms and oxygen atoms appears near -7eV, indicating that chemical adsorption is formed between water molecules and titanium dioxide, which in turn affects its gas sensing performance. When the number of adsorbed water molecules increases, such as Figure 13-14 As shown, the peak area of the new energy level formed by water molecules gradually increases, indicating that the number of chemical bonds formed between water molecules and TiO2 increases.
[0043] (3) H2S was used as the target detection gas, and the H2S concentration in the test was controlled by a mass flow controller. An alumina plate with a gold electrode and a heating layer was used as the gas sensor substrate, and metal-doped TiO2 was used as the gas sensitive material. During the test, the humidity level varied from 35%RH-85%RH and was calibrated by a hygrometer. During the test, the humidity level varied from 35%RH-85%RH and was calibrated by a hygrometer. The effects of the type and content of metal atom doping on the H2S response value of the gas sensor at different humidities were recorded. Fig.15 As shown in the figure, as the ambient humidity increases, at low humidity, the iron-doped TiO2 gas sensor maintains a high response value to H2S, and as the humidity exceeds 50%RH, the response value of the gas sensor drops rapidly. However, when the humidity increases further, the response value of the gas sensor shows another peak, and the response value reaches the highest value at 70%RH. Combined with the above simulation results, the trend of the bandgap width change and the PDOS analysis results are consistent with the experimental results.
[0044] In summary, the present invention establishes a TiO2 crystal model and a TiO2 crystal plane at the atomic level, and uses the TiO2 crystal model to perform computational experiments on its crystal structure, bandgap width, electronic state density and other characteristics. Through the TiO2 crystal plane, the crystal surface structure, energy band, state density, optics and gas-sensitive properties after molecular adsorption and / or doping with metal atoms can be experimented, and the influence of metal atom doping modification and environmental humidity changes on TiO2 characteristics can be simulated. At the same time, from the perspective of gas-sensitive response mechanism, the performance of the gas sensor is analyzed, which greatly reduces the experimental time and cost. The process of the present invention is not limited by experiments, and the test cycle can be greatly shortened. Existing experimental phenomena can be explained at the atomic level, and unnecessary experimental costs can be reduced by calculating and designing materials, and the performance of the gas sensor can be effectively improved, which provides important theoretical guidance and technical support for the improvement of the performance of the gas sensor.
Claims
1. A simulation method for verifying the mechanism of multiple factors affecting the gas sensing performance of TiO2, characterized in that: Including the establishment of TiO2 crystal model, the establishment of TiO2 crystal surface and the experiment of doping and gas sensing characteristics; The TiO2 crystal model is a supercell of eight anatase phase TiO2 crystal cells; The TiO2 crystal plane is established by cutting the supercell to obtain the TiO2 (101) plane, and adding a vacuum layer with a size of 11.15Å×7.60Å×17.428Å; the TiO2 crystal plane is doped by adsorbing water molecules and / or doping metal atoms on the TiO2 (101) plane; Metal atoms are doped on the TiO2 (101) surface, replacing the Ti atom in the TiO2 (101) surface with a metal atom; The gas sensing property test is to use an aluminum oxide plate with a gold electrode and a heating layer as a gas sensor substrate, and use TiO2 doped with molecular adsorption and / or metal atoms as a gas sensitive material, and record the influence of the metal atom doping type and / or water molecule content on the response value of the gas sensor under different humidity; The supercell is simulated by Materials studio software, with lattice constants a0=b0=378.4pm, c0=951.5pm, space group D4h19-I41 / amd, plane wave shear energy of 340eV, K-point of 2×3×1; the overall energy level of the cell is better than the minimum of 1×10 -5 eV·atom -1 The distance deviation between atoms is 0.001°A; SCF is used to solve the Kohn-Sham equation and energy functional to optimize the TiO2 crystal model.
2. The simulation method for verifying the mechanism of multiple factors affecting the gas sensing performance of TiO2 according to claim 1, characterized in that: The doping of the TiO2 crystal surface is to increase the concentration of water molecules in the TiO2 (101) surface doped with metal atoms.
3. The simulation method for verifying the mechanism of multiple factors affecting the gas sensing performance of TiO2 according to claim 1, characterized in that: The gas sensing property test uses H2S as the target detection gas. The H2S concentration in the test is controlled by a mass flow controller. During the test, the humidity level varies from 35%RH to 85%RH and is calibrated by a hygrometer.
4. The simulation method for verifying the mechanism of multiple factors affecting the gas sensing performance of TiO2 according to claim 1, characterized in that: The metal atom is a Co atom, a Fe atom or a Zn atom.